Childhood primary myelofibrosis presented with headache, splenomegaly, and severe thrombocytosis: A case report - Athanasios Tragiannidis; Athanasia Apsemidou; Ioannis Liampas; Triantafyllia Koletsa (Indian Journal of Medical and Paediatric Oncology)
Primary myelofibrosis (PMF) is a clonal disorder of a multipotent hematopoietic progenitor cell that occurs predominantly in the elderly age group. We report here an 11-year-old girl who presented with headache, fever, and splenomegaly. Full blood cell count revealed severe thrombocytosis. Laboratory and radiology examinations excluded the diagnosis of essential/reactive thrombocytosis. Bone marrow biopsy showed megakaryocytic hyperplasia, reticulin and collagen fibrosis, and erythroid and myeloid hypoplasia, findings compatible to PMF. The patient was put symptomatically on hydroxyurea and hydration due to thrombocytosis and platelet number decreased. Hematopoietic stem cell transplantation was scheduled to avoid delaying definitive therapy and secondary complications such as infections and transfusion dependency. To the best of our knowledge, this is the first reported case of PMF in childhood in Greece.